2018
DOI: 10.1096/fj.201801292r
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐mediated lysosomal reacidification restores mitochondrial turnover and function in β cells under lipotoxicity

Abstract: Chronic exposure of pancreatic β cells to high concentrations of free fatty acids leads to lipotoxicity (LT)‐mediated suppression of glucose‐stimulated insulin secretion. This effect is in part caused by a decline in mitochondrial function as well as by a reduction in lysosomal acidification. Because both mitochondria and lysosomes can alter one another's function, it remains unclear which initiating dysfunction sets off the detrimental cascade of LT, ultimately leading to β‐cell failure. Here, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…For the studies presented here, only the mCherry fluorophore was excited and recorded. 2mtGCaMP6m construct was a generous gift from Diego De Stefani 26 and the adenoviral particles were prepared as described previously 50,52 .…”
Section: Methodsmentioning
confidence: 99%
“…For the studies presented here, only the mCherry fluorophore was excited and recorded. 2mtGCaMP6m construct was a generous gift from Diego De Stefani 26 and the adenoviral particles were prepared as described previously 50,52 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the restoration of lysosomal pH by lysosome-targeted nanoparticles reinstates mitophagy in pancreatic cells exposed to high concentrations of free fatty acids [32]. These findings indicate that, at least under lipotoxic conditions, mitochondrial dysfunction develops downstream of lysosomal alkalization and that recovery of lysosomal acidity restores MQC [32].…”
Section: Introductionmentioning
confidence: 91%
“…On a similar note, ablation or pharmacological inhibition of apoptosis inducing factor (AIF), OPA1, or phosphatase and tensin homolog (PTEN)-induced putative kinase 1 (PINK1) in neurons impairs lysosome activity, thereby causing accrual of autophagic substrates [31]. Moreover, the restoration of lysosomal pH by lysosome-targeted nanoparticles reinstates mitophagy in pancreatic cells exposed to high concentrations of free fatty acids [32]. These findings indicate that, at least under lipotoxic conditions, mitochondrial dysfunction develops downstream of lysosomal alkalization and that recovery of lysosomal acidity restores MQC [32].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin content was also measured in all the treatment conditions (Figure S3, Supporting Information), and it was not significantly altered between the conditions, indicating that PLGA NPs unlikely affected insulin release from granules. It has been reported that dysfunctional lysosomal acidification in pancreatic beta cells leads to an increase in mitochondrial mass and a decrease in mitochondria turnover and mitochondrial respiratory capacity . This decrease in mitochondrial respiratory results in decreased adenosine triphospate (ATP) production, and eventually leads to decreased GSIS and beta cell dysfunction .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that dysfunctional lysosomal acidification in pancreatic beta cells leads to an increase in mitochondrial mass and a decrease in mitochondria turnover and mitochondrial respiratory capacity . This decrease in mitochondrial respiratory results in decreased adenosine triphospate (ATP) production, and eventually leads to decreased GSIS and beta cell dysfunction . Therefore, repairing lysosomal function with PLGA NPs provides an opportunity to restore mitochondrial function with ATP production affording improved GSIS and beta cell function.…”
Section: Resultsmentioning
confidence: 99%